Lean Principles Implementation in Construction Management: A One Team Approach - Fahmy, Mahmoud (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Lean in construction is a relatively new approach in delivering construction projects. The Lean approach has been introduced to tackle the phenomenal construction projects delays and budget overruns. This paper shall be discussing how the implementation of the Lean approach in construction management processes can improve construction projects’ delivery. The paper argues that the Lean approach in the construction industry context revolves around people rather than processes as in the manufacturing industry context. Therefore, the cornerstone of the Lean approach in construction is creating a One Team out of the multiple typical rivals in the construction industry: Owner, architect / engineer, operator and contractor with all taking into consideration the end user. While the ‘Lean’ concept is manufacturing tackled processes to achieve the ‘Lean’ goal; in construction the ‘Lean’ approach is tackling the interaction between people and entities. The interaction between people is addressed by the ‘Lean construction’ planning tool: The last planner system; while the interaction between entities is addressed by contractual forms of agreement with the most influential being: Alliance contracting. The paper uses a major infrastructure project ‘Sydney Desalination Plant’ which started in June 2007 and completed in January 2010 as a successful example of Lean approach implementation, although the term ‘Lean’ was never used then by the parties involved in the project. The paper draws on the first-hand experience of the author in the construction industry including the participation in the delivery of the ‘Sydney Desalination Plant’ used as example of a Lean project.